Pengelolaan Pembelajaran Menggambar Busana Di SMK Negeri 1 Gantiwarno Klaten - Wijayanti, Nunuk; , Prof. Dr. Bambang Sumardjoko; , Dr. Suyatmini, M.Si (2016)
This study have three aims to describes: 1) lesson planning, 2) learning implementation, 3) evaluation of fashion drawing learning in SMK N 1 Gantiwarno Klaten. This research is qualitative research with etnography design. Data was collected by observation, interview, and documentation. Data analysis use Milles and Huberman analysis are data reduction, data display and verification. The validity of the data using data and methods triangulation.Results of this research there are three things about: 1) Lesson plans of drawing fashion in SMK Negeri 1 Klaten Gantiwarno done by teachers prepare learning device, subject matter from various sources, learning support facilities such as VCD, LCD and drawing paper, students prepare textbooks and fashion drawing tool, homework that has provided teachers in previous lessons and the teacher's task to collect pictures of fashion. 2) Implementation of fashion drawing learning in SMK Negeri 1 Klaten Gantiwarno done by giving apperception on the development of clothing design is very rapid, conveying some progress communications equipment that contain a fashion like magic camera, plus camera, and some games that contain with a variety of fashion pictures, assign tasks to students to draw fashion, teach students starting fashion drawing, students practice fashion drawing on drawing paper, ask teachers about fashion drawing, holding discussions with seatmate to design fashion drawing. 3) Evaluation of fashion drawing learning in SMK Negeri 1 Klaten Gantiwarno can be described that students learn before facing the daily tests, teachers provide daily tests in a semester as much as 5 times and drawing practical assignments, teachers make daily tests of multiple choice questions and record the attitudes and behavior of students to determine student learning discipline in the school environment.